Instituto Valentín de Foronda como un espacio de gestación, desarrollo y consolidación de nuevos investigadores - Amado Castro, Víctor Manuel (Huarte de San Juan. Geografía e Historia, 2015)
Since its inception twenty years ago the Institute of Social History Valentín de Foronda has given an academic working coverage to several promotions of professionals of the history. In the present article, a brief review of this group of professionals who have developed their work at the Institute is addressed. Furthermore, this text gives a brief prosopographical report about these researchers, as an example of the evolution of the same Institute. This current text ends providing a set of conclusions and some challenges what might be faced by the Institute of Social History Valentín de Foronda in the twenty-first century.